Low-Molecular Weight Protamine Overcomes Chondroitin Sulfate Inhibition of Neural Regeneration - Kulesskaya, Natalia; Mugantseva, Ekaterina; Minkeviciene, Rimante; Acosta, Natalia; Rouhiainen, Ari; Kuja-Panula, Juha; Kislin, Mikhail; Piirainen, Sami; Paveliev, Mikhail; Rauvala, Heikki (Frontiers in Cell and Developmental Biology, 2022)
Protamine is an arginine-rich peptide that replaces histones in the DNA-protein complex during spermatogenesis. Protamine is clinically used in cardiopulmonary bypass surgery to neutralize the effects of heparin that is required during the treatment. Here we demonstrate that protamine and its 14–22 amino acid long fragments overcome the neurite outgrowth inhibition by chondroitin sulfate proteoglycans (CSPGs) that are generally regarded as major inhibitors of regenerative neurite growth after injuries of the adult central nervous system (CNS). Since the full-length protamine was found to have toxic effects on neuronal cells we used the in vitro neurite outgrowth assay to select a protamine fragment that retains the activity to overcome the neurite outgrowth inhibition on CSPG substrate and ended up in the 14 amino acid fragment, low-molecular weight protamine (LMWP). In contrast to the full-length protamine, LMWP displays very low or no toxicity in our assays in vitro and in vivo. We therefore started studies on LMWP as a possible drug lead in treatment of CNS injuries, such as the spinal cord injury (SCI). LMWP mimicks HB-GAM (heparin-binding growth-associated molecule; pleiotrophin) in that it overcomes the CSPG inhibition on neurite outgrowth in primary CNS neurons in vitro and inhibits binding of protein tyrosine phosphatase (PTP) sigma, an inhibitory receptor in neurite outgrowth, to its CSPG ligand. Furthermore, the chondroitin sulfate (CS) chains of the cell matrix even enhance the LMWP-induced neurite outgrowth on CSPG substrate. In vivo studies using the hemisection and hemicontusion SCI models in mice at the cervical level C5 revealed that LMWP enhances recovery when administered through intracerebroventricular or systemic route. We suggest that LMWP is a promising drug lead to develop therapies for CNS injuries.